The controlling role of sodium and carbonate on the atmospheric corrosion rate of aluminum. (December 2017) - Schaller, Rebecca; Jove-Colon, Carlos; Taylor, Jason; Schindelholz, Eric
Abstract Aluminum and aluminum alloys are widely used in many outdoor applications due to their inherent corrosion resistance attributed to the formation of a protective oxide layer. While corrosion rates are generally considered low for aluminum in many atmospheric environments, understanding of the corrosion performance over time is necessary to predict the cost, safety, and esthetics of these materials. The vast majority of the knowledgebase of atmospheric aluminum corrosion is built on environment–response relationships; often based on statistical correlation of corrosion rate data with atmospheric environmental conditions. However, there is still a limited mechanistic understanding of corrosion processes associated with this linkage. This lack in knowledge prevents interpretation and limits the extrapolation of these statistical datasets for prediction purposes. Here, the mechanistic dependence of aluminum corrosion rate on salt loading is explored through complimentary experimental and theoretical analysis relating corrosion rate to electrolyte chemistry, volume and corrosion products. From these results a reaction pathway is proposed for the atmospheric corrosion of aluminum that accounts for the governing effects of CO2 and salt loading on corrosion rate. This reaction pathway provides a new perspective that highlights the importance of the formation and growth of dawsonite (NaAlCO3 (OH)2 ), and the subsequent gettering of sodium from the electrolyte leading to the stifling of corrosion kinetics. This study highlights the importance of accounting for the dynamic physical and chemical state of the electrolyte during corrosion in process models and measurement techniques to better understand and predict atmospheric corrosion behavior. Aluminium: trapped sodium stops further degradation Corrosion of aluminium in a saline atmosphere hinges so much on carbon dioxide and sodium that it can become stifled after corrosion products build up. A team led by Eric Schindelholz at the Sandia National Laboratories in New Mexico, USA, took time-resolved gravimetric measurements of commercial aluminium loaded with sodium chloride and characterized the corrosion product weight and volume with time. The aluminium corroded by forming sodium aluminium carbonate - dawsonite—which trapped the sodium on the surface, leading to the salt water drying. This caused a decrease and, in some cases, stifled corrosion at the aluminium surface. While dawsonite has usually been ignored in aluminium corrosion, research into lesser-known corrosion reaction pathways may help us better understand and predict atmospheric and environmental corrosion.